Phylogenetic analysis of feline coronavirus isolates from healthy cats in Malaysia - Sharif, Saeed; Arshad, Siti Suri; Bejo, Mohd Hair; Omar, Abdul Rahman; Allaudin, Zeenathul Nazariah; Hafidz, Mohd Afzal (2009)
Feline Coronaviruses (FCoVs) are widespread in cat populations throughout the world. Infection with FCoV results in a diverse range of signs from no clinical symptom at all to a highly fatal immune-mediated disease called feline infectious peritonitis (FIP). It has been speculated that mutations in the FCoV genome induce virulent variants in infected cats and lead to the development of FIP. In present study, a 223 bp region of 3’UTR of four FCoVs isolated from healthy cats was amplified by a one-step reverse transcriptase polymerase chain reaction (RTPCR) and sequenced. The nucleotide sequences were aligned with those of FCoV reference strains and identity and phylogenetic tree were determined. The obtained sequence of Malaysian FCoV isolates revealed 94.6 % identity with a few point mutations. The extent of identity decreased to 86.6 % when compared with the sequence of other FCoV strains/isolates. The overall phylogenetic analysis based on this comparison showed that there are two distinct clusters. The four local isolates are shown to be closely related and fall together in one of the clusters. This study provided the first genetic data on FCoV isolates from Malaysia.